2017
DOI: 10.1111/jgs.14828
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Transitional Care Services for Chronically Ill Older Patients: A Systematic Evidence Review

Abstract: Transitions in care from hospital to primary care for older patients with chronic diseases (CD) are complex and lead to increased mortality and service use. In response to these challenges, transitional care (TC) interventions are being widely implemented. They encompass education on self-management, discharge planning, structured follow-up and coordination among the different healthcare professionals. We conducted a systematic review to determine the effectiveness of interventions targeting transitions from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
184
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(208 citation statements)
references
References 157 publications
(457 reference statements)
6
184
1
7
Order By: Relevance
“…In the wider literature, communication skills training is a recognized component of self‐management . Evidence of training, however, is not apparent in existing transition interventions for older people, and in the studies in the current review, use of such skills was not apparent. Reasons are likely to vary, but the hospital setting itself is likely to be a factor.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the wider literature, communication skills training is a recognized component of self‐management . Evidence of training, however, is not apparent in existing transition interventions for older people, and in the studies in the current review, use of such skills was not apparent. Reasons are likely to vary, but the hospital setting itself is likely to be a factor.…”
Section: Discussionmentioning
confidence: 64%
“…Interventions aiming to support older people to transition from hospital to home have been the subject of numerous systematic reviews . Self‐management and/or education, as a way of empowering individuals to be involved in and take control of their care, was the second most common component of these multicomponent interventions .…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced emergency planning and greater “on call” presence of homecare staff could help reduce observation and ED visits . The results of this study are consistent with previous literature evaluating CTPs . An important contribution of this study is quantification of the role of NP and SW home visits, which had been a gap .…”
Section: Discussionmentioning
confidence: 99%
“…CTPs are described extensively in the literature, with models ranging from unimodal, disease‐specific interventions to multimodal comprehensive care coordination models. Reviews of CTPs suggest that multimodal, multidisciplinary interventions spanning time and settings are most effective for achieving positive outcomes . A seminal randomized controlled trial of the Care Transitions Intervention demonstrated that a multimodal model can reduce hospital readmissions of individuals with complex care needs .…”
mentioning
confidence: 99%
See 1 more Smart Citation